NILAI-NILAI PENDIDIKAN DALAM NOVEL SOKOLA RIMBA KARYA BUTET MANURUNG - Fita Delvia Saragih; Yundi Fitrah; Irma Suryani (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2015)
The purpose of this study is to describe the values ​​of education contained in the novel Sokola Rimba by Butet Manurung which refers to nine aspects of educational value, namely: faith and piety to God Almighty, noble, healthy, knowledgeable, skilled, creative , independent, democratic, and responsible. The method used in this research is qualitative descriptive method with qualitative approach. The source of data in this research is the novel Sokola Rimba with data in the form of words, sentences, paragraphs, and discourse in the form of narration or dialogue in accordance with the problems studied. The data that has been collected is then analyzed using an interactive-dialectical model. Checking the validity of data is done by Triangulation technique, which is a method by collecting similar data from available data sources. The result of the research shows that the novel of Sokola Rimba by Butet Manurung has educational values. namely, believing and cautious to God Almighty, noble, healthy, knowledgeable, capable, creative, independent, democratic, and responsible. The value of education is expressed implicitly and explicitly in the narrative and dialogue presentation. The conclusion of the research in the novel Sokola Rimba by Butet Manurung proved to have significant educational values ​​for human life. The values ​​of education contained in the novel is the value of faith education and cautious to God Almighty, the value of noble education, the value of healthy education, the value of tertiary education, the value of skilled education, the value of creative education, the value of independent education, the value of democratic education , and the value of education is responsible.